The Harmony of Meter and Emotion in the Odes of Anvari Abivardi (With a Look at the Poems of His Master, Abol Faraj Runi) - Maryam Khalili Jahantigh; Mohammad Barani; Leila Shakibaei (Literary Arts)
In this study, harmony is used in the general sense of compromise, coordination, and unity. Music is one of the constructive elements in the formation and structure of poetry, which highlights the speech and has a close relationship with the poet's emotions and intentions. By choosing an external melody that matches the meaning, that is, rhythm as one of the branches of music, the poet increases the effect of his poem and promotes its artistic and literary value. This leads to the communication of the meaning and the veiled emotion, in the deep structure, of the poem. Consequently, it will form spiritual coherence and phonetic melody by employing other poetic musical devices. The purpose of this research is to investigate the quality and quantity of the types of bahrs (prosodic meters), and specifically, to analyze the degree of their coordination with the emotions and feelings of Anvari in his odes. This research is done using the descriptive-analytical method and library sources. In the selected odes, 9 bahr (prosodic meters) and 37 meters are used, with the highest frequency, respectively, for Ramal, Khafif, Hazaj, Mozare, and Mojtath. Metric variations, arrangement of syllables with distinct quality, that is, paying attention to the type of syllables in the speech structure, such as long and elongated syllables or short and moving syllables, and the low use of poetic license has resulted in admirable coordination with the poet’s emotions of contemplation and hesitation, sadness, and delight. The use of the above cases in Anvari’s poetry has led to the rise of emotions in both individual and social aspects, giving his poetry the opportunity to get out of the shadow of pure imitation and praise. This, even, prevents him from imitating a leading poet, Abol Faraj Runi, in changing his poetic style. Abul Faraj's intellectual horizon only appears in the domain of eulogy and personal gain; however, Anvari is not indifferent to social issues and events. Thus, he, unlike his master, has established a sort of coordination between meter and emotion.